Safeguarding the Rights of Indonesian Migrant Workers: Legal Counseling in Pabuaran and Sindangsari Assisted Villages - Hilton Tarnama Putra M; Danial Danial; Surya Anom; Belardo Prasetya Mega Jaya; Mokhamad Gisa Vitrana; Hera Susanti; Yeliana Septiani Noor; Khotimah Estiyovionita; Tiara Destia Herman (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2023)
The International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, established in 1990, provides general regulations for the legal protection of migrant workers. Indonesia has adopted this convention by ratifying it through Law No. 6 of 2012 on the Ratification of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families. Further specific regulations on the protection of Indonesian migrant workers are outlined in Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers. The protection of Indonesian migrant workers involves three stages: pre-employment protection, protection during employment, and post-employment protection. These stages require direct involvement from the state in providing adequate protection. The International Law Department of the Faculty of Law at Universitas Sultan Ageng Tirtayasa, in collaboration with the Pabuaran and Sindangsari Villages in Serang Regency, Banten Province, conducted a community service program that offered legal services to villages that serve as sources of migrant workers within the Untirta Sindangsari campus.